Pengaruh Media Pembelajaran Kahoot Terhadap Motivasi Dan Hasil Belajar Siswa Pada Mata Pelajaran IPS Kelas V SD Negeri 01 Fena Fafan - Hukunala, Desy; Ritiauw, Samuel P.; Ritiauw, Leonid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the difference between learning outcomes before and after using the Kahoot application in social studies lessons in Grade V elementary school. The research used a quantitative research design with a quasi-experimental approach and a non-equivalent control group design. The results showed that there was a significant increase in learning outcomes and motivation after using Kahoot media in Grade V students at Negeri 01 Fena Fafan Elementary School.